Implant cap / Dr Nagham Mohammed Abdullah and Ibrahim Muhamadi - Abdullah, Nagham Mohammed; Muhamadi, Ibrahim (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
This is an idea to manufacture a cap or cover for the orthodontic mini screws or mini implants that are inserted in the patient mouth during orthodontic treatment. Orthodontic mini screws and mini implants has become a very helpful tool for orthodontists in their everyday work. However mini screws can cause serious trauma and ulcers to the tongue and soft tissue, and this will affect patient cooperation and acceptance of this treatment modality and ultimately jeopardize treatment success. This new idea of cap design will help to protect the soft tissue from trauma and ulceration and increase patient cooperation and acceptance of this treatment modality. Also covering the mini screw may protect the surrounding soft tissue from inflammation which is considered a cause of failure for mini screw. This implant cap design which was proposed to have an elliptical or ovoid shape and have the dimensions of 4mm in height and 6 mm in width can best be produced using medical silicone as this material is biocompatible, highly inert and has been used for decades in different medical applications. The production technique could be silicon injection molding because of the cap small size and the precise shape needed. The cap can easily be pressed on the implant or screw head